Catalyst-Free Photoinduced C–C Bond Formations - Bera, Shyamal Kanti; Bhanja, Rosalin; Mal, Prasenjit (Synthesis, 2023)
Use of sustainable energy sources in synthetic organic chemistry has become one of the most popular research topics due to environmental pollution and global warming. In this review, we discuss photocatalyst-free and transition-metal-free light-induced reactions for the construction of carbon–carbon (C–C) bonds. The reaction systems discussed here are C–C bond formation via carbene intermediates, radical intermediates, and miscellaneous reactions via cyclization.1 Introduction2 C–C Bond Formation via Carbene Intermediates3 C–C Bond Formation via Radical Intermediates4 Miscellaneous C–C Bond Formation via Cyclization5 Conclusion
Keywords: C–C bond formation; catalyst-free; transition-metal-free; photoinduced; visible light; carbene; radical